1990
DOI: 10.1111/j.1651-2227.1990.tb11446.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Cyst and Vacuum Extraction

Abstract: A single case of growing skull-fracture and intracranial porencephalic cyst caused by vacuum extraction is on record (1). We report an infant who developed a large extracranial pseudomeningocele after tedious ventouse extraction.The six-month-old male infant was first examined at our outpatient clinic because of a large rapidlygrowing cranial bulge ( Fig. 1). He was born in another hospital by a nulliparous mother after an uneventful pregnancy. Labour had been induced electively, at 39 weeks of gestation. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Falling appears to be the most frequent cause of injury. Motor vehicle accidents, child abuse, birth injuries, and previous cranial surgery can also lead to GSF [4,7,13,25,[34][35][36][37][38][39][40][41][42]. Moss et al [43] even reported intrauterine GSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falling appears to be the most frequent cause of injury. Motor vehicle accidents, child abuse, birth injuries, and previous cranial surgery can also lead to GSF [4,7,13,25,[34][35][36][37][38][39][40][41][42]. Moss et al [43] even reported intrauterine GSF.…”
Section: Discussionmentioning
confidence: 99%
“…Moss et al [43] even reported intrauterine GSF. Neurological deficits such as hemiparesis, squinting, and visual field defects may accompany the scalp swelling [4,7,16,27,30,35,37,41,44,45]. Symptoms and signs may also vary with the growing fracture's location.…”
Section: Discussionmentioning
confidence: 99%
“…The case reported by Hansen et al [2] was explained by repositioning the vacuum cup too anteriorly, thereby disrupting the coronal suture. The case decribed by Vanhaesebroeck et al [3] was complicated by 'multiple episodes of cup detachment'. Also in our case VE was not without difficulty, with the possibility of the cup being placed too anteriorly resulting in abnormal force vectors.…”
Section: Discussionmentioning
confidence: 98%
“…In almost all reported cases the cause of injury was a fall from a height or a car accident and it takes several months to years for the clinical picture to evolve [11]. Only 5 cases have been described following traumatic birth: 2 after forceps delivery [12] and 3 after VE [2,3]. One congenital GSF after prenatal trauma has also been described [ 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation